EFEKTIVITAS KINERJA PEGAWAI BIDANG INFORMASI DAN MUTASI PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH KOTA PALU - Mustapa, Ilham Akbar; Hasbullah, Hasbullah; Aksan, Sitti Chaeriah (Katalogis, 2020)
The Research aimed to analyze the employee effectiveness of Information Division and Employee Mutation at Staffing Agency and Human Resource Development of Palu. The main theories that become the reference in this research are the effectiveness theory by Richard M. Steers (1980: 192), in measuring the effectiveness of employee's work includes 3 aspects: 1) adaptability; (2) work performance; and (3) job satisfaction. The research method used descriptive-qualitative approach. The location of this research is in the Staffing Agency and Human Resource Development of Palu with informants amounting to 5 people who were selected purposively. The data collection was conducted through interview, observation, and documentation. The data analysis techniques used the Interactive model of Miles and Huberman. Based on the results of the research by looking at the effectiveness of the performance of employee in Information Division and Employee Mutation at Staffing Agency and Human Resource Development of Palu can be seen from 3 aspects, it was adaptability, work performance and job satisfaction aspects, in which the overall performance of employees in Information Division and Employee Mutation at Staffing Agency and Human Resource Development of Palu has been effective.